Future ready : your organization's guide to rethinking climate, resilience, and sustainability - Lewis, Tom (Executive); MacGregor, Alastair (Aly); Swann, Stacy (John Wiley & Sons, Inc., 2023)
"Whether readers are starting out on the sustainability journey, looking to build institutional support, or working to accelerate action against ambitious commitments, Future Ready will serve as an essential guide to setting (or upleveling) strategy, driving implementation in complex operating environments, engaging stakeholders, measuring impact, and communicating the results. Grounded in nearly 150 years of experience, this book will equip readers with unprecedented insights into headline grabbing mega-projects and a behind-the-scenes look at unsung efforts that are revolutionizing the very concepts of sustainability and resilience."--